2022
DOI: 10.1007/s12035-022-02932-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Sequelae of COVID-19 in Experimental Mice

Abstract: We recently reported acute COVID-19 symptoms, clinical status, weight loss, multi-organ pathological changes, and animal death in a murine hepatitis virus-1 (MHV-1) coronavirus mouse model of COVID-19, which were similar to that observed in humans with COVID-19. We further examined long-term (12 months post-infection) sequelae of COVID-19 in these mice. Congested blood vessels, perivascular cavitation, pericellular halos, vacuolation of neuropils, pyknotic nuclei, acute eosinophilic necrosis, necrotic neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 66 publications
2
47
0
Order By: Relevance
“…These mice exhibit pronounced lung injury with mortality rates ranging from 40% to 60% between days 7 and 12 post-infection [ 14 ]. Upon examination at the time of death, the lungs display severe interstitial pneumonitis characterized by interstitial inflammatory reactions, along with substantial infiltrations of lymphocytes and macrophages [ 15 , 16 , 17 , 18 ]. Additionally, investigations into the livers of MHV-1-infected A/J mice disclose evidence of severe hepatic congestion, mirroring observations in humans infected with SARS-CoV-2 [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…These mice exhibit pronounced lung injury with mortality rates ranging from 40% to 60% between days 7 and 12 post-infection [ 14 ]. Upon examination at the time of death, the lungs display severe interstitial pneumonitis characterized by interstitial inflammatory reactions, along with substantial infiltrations of lymphocytes and macrophages [ 15 , 16 , 17 , 18 ]. Additionally, investigations into the livers of MHV-1-infected A/J mice disclose evidence of severe hepatic congestion, mirroring observations in humans infected with SARS-CoV-2 [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“… 31 Mucin inhibits coronavirus infection via its glycan in an organoid in vitro model. 32 , 33 Mucin mRNA in the blood or respiratory tissue could be a marker for SARS-CoV-2 infection and COVID-19 severity. 34 Our previous study showed that the number of mucin-secreting cells decreases in some GI tract fragments at the early stage of SARS-CoV-2 infection, but gradually increases at the late stage of infection in the NHP model, indicating that mucin correlates with the recovery of the disease caused by SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported increased reactive astrocytes and microglia, hyperphosphorylated TDP-43 and tau, and decrease in synaptic protein synaptophysin-1 and defective neuronal integrity in A/J mice 12 months post-infection. Although the study recapitulates long-term sequelae of COVID-19, a mouse hepatitis virus 1 (MHV-1) was used in this study 48,49 .…”
Section: Discussionmentioning
confidence: 99%